Social Psychology in Organizations: Advances in Theory and ResearchSocial Psychology in Organizations: Advances in Theory and Research, edited by Murnighan J. Keith. Englewood Cliffs, NJ: Prentice-Hall, 1993. 415 pp., cloth. - Gersick, Connie J. G. (Academy of Management Review, 1994)
The article reviews the book “Social Psychology in Organizations: Advances in Theory and Research,” edited by J. Keith Murninghan.